What’s in My Profile: VKontakte Data as a Tool for Studying the Interests of Modern Teenagers - Polivanova, Katerina; Smirnov, Ivan (Voprosy obrazovaniya / Educational Studies Moscow, 2017)
Children’s interests play a key role in their psychological development. However, research in this field is associated with serious methodological problems, as it has traditionally used questionnaire surveys that cannot adequately describe the diverse and dynamic world of interests of a developing person. The article suggests using the information on VKontakte communities followed by teenagers, in order to explore their interests. Apart from being comprehensive, Vkontakte data is, unlike questionnaire answers, also uncensored. The method’s potential demonstrated through the example of a Moscow school with 674 students following 20,203 various VKontakte communities. It reveals that teenagers’ interests vary depending on their gender, age, and academic performance. The degree of such variance is demonstrated on an extended set of data on the interests of 290,182 VKontakte users. It transpires that communities followed by teenagers predict with high accuracy not only their gender (97%) and age (98%) but also the performance of the schools they attend (83%). The findings point to the heterogeneity of age-related behavior patterns, in particular to their correlation with gender and academic achievements. Acknowledgement of the heterogeneity of interests and the diversity of age-related behavior patterns creates conditions for the further development of student-centered education, in the absence of which education is becoming more and more alienated from real life, ignoring the interests of real people.